Efektivitas Mekanisme Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang dalam Perspektif Hukum Positif Indonesia - Jannah, Rohmatul; Riyandra, Kania Putri; Widyaningrum, Najwa Aulia; Yazdaniar, Athalla Fikra (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The crime of money laundering poses a serious threat to Indonesia’s economic stability and the integrity of its financial system. Although Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering has been enacted, the effectiveness of its implementation continues to face various challenges, such as the complexity of financial transactions, limitations in law enforcement resources, and low public awareness. This study aims to analyze the effectiveness of the mechanisms for preventing and eradicating money laundering from the perspective of Indonesia’s positive law. The research method employed is normative juridical, using a statutory and case analysis approach. The results of the study indicate that although a legal framework is in place, its effectiveness needs to be enhanced through inter-agency coordination, capacity building of human resources, and adaptation to technological developments.